Toward an Interoperable National Hazards Events Database for South Africa - Davis-Reddy, Claire; Hilgart, Amelia (Frontiers in Climate, 2021)
South Africa’s National Disaster Policy and international reporting requirements including the Sendai Framework for Disaster Risk Reduction 2015-2030 and the Sustainable Development Goals require reporting databases on disaster losses in order to facilitate evidence-based decisions and actions. Data fragmentation, gaps in data availability, spatial and temporal aggregations, poor data quality, and lack of metadata are South Africa’s most significant challenges to improved risk management planning, mitigation, and disaster loss reporting. Researchers need to discover and access scale- and task-appropriate data in order to integrate into their models or analyses. Although there is a growing number of international and national initiatives aimed at publishing disaster loss data, open access, integration and reuse remains difficult due to interoperability barriers to working with datasets. The current COVID-19 Pandemic has placed a number of these challenges at the forefront with the issues of access to trustworthy data coming under scrutiny. We consider the current sources of disaster data for South Africa and present our recommended solutions built into an online disaster reporting prototype system.